Islamic Divorce in the Twenty-First Century : A Global Perspective. - Stiles, Erin E. (Politics of Marriage and Gender: Global Issues in Local Contexts Ser., 2022)
Islamic Divorce in the 21st Century shows the wide range of Muslim experiences in marital disputes and in seeking Islamic divorces. For Muslims, having the ability to divorce in accordance with Islamic law is of paramount importance. However, Muslim experiences of divorce practice differ tremendously. The chapters in this volume discuss Islamic divorce from West Africa to Southeast Asia, and each story explores aspects of the everyday realities of disputing and divorcing Muslim couples face in the twenty-first century. The book's cross-cultural and comparative look at Islamic divorce indicates that Muslim divorces are impacted by global religious discourses on Islamic authority, authenticity, and gender; by global patterns of and approaches to secularity; and by global economic inequalities and attendant patterns of urbanization and migration. Studying divorce as a mode of Islamic law in practice shows us that the Islamic legal tradition is flexible, malleable, and context-dependent.